Endeavor to establish the truth in civil proceedings - Jankowski, Janusz (Acta Universitatis Lodziensis. Folia Iuridica, 2014)
In the literature and jurisprudence there are distinguished two opposite principles ruling over revealing the truth: a material truth principle (objective) and a formal truth principle (procedural). In the proceedings based on the material truth principle, judicial decisions in the matter of the actual state should reflect the reality. The judge aims to clarify all circumstances essential to solve a case in order to reveal a really existing legal relation bounding both parties to litigation. On the other hand, in proceedings based on the formal truth principle, judicial decisions in the matter of the actual state should only reflect the factual material and evidence gathered by the parties. In the study there is presented an evolution of norms and doctrinal opinions in the matter of the endeavor to establish the truth in civil proceedings connected with amendments to the Civil Procedure Code in 1996, 2000, 2005 and 2012.